2023
DOI: 10.58905/saga.v1i3.69
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Organoleptic Quality of Free-Gluten Dry Noodles from Sorghum (Sorghum bicolor) and Modified Cassava Flour with Different Drying Temperature

Ayyu Nisa’ Rizky N.F.,
Fadjar Kurnia Hartati,
Nunuk Hariyani

Abstract: Dry noodles are widely commercialized thanks to their durability and practicality for consumption as side dishes or staples to replace rice. The development of dry noodles is robustly conducted, mainly by substituting its main ingredient of wheat flour to local staple flour with similar or better nutritional value and characteristics compared to wheat flour and gluten-free as well. Some alternatives are sorghum (Sorgum bicolor) flour and mocaf (Modified cassava flour). Applying the correct drying temperature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, jack bean flour concentration proportion does not exhibit any discernible influence on water content. This is because the starch content of jack bean flour is low; therefore, the hydroxyl groups that influence optimal water absorption capacity are also common [24] .…”
Section: Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, jack bean flour concentration proportion does not exhibit any discernible influence on water content. This is because the starch content of jack bean flour is low; therefore, the hydroxyl groups that influence optimal water absorption capacity are also common [24] .…”
Section: Moisture Contentmentioning
confidence: 99%
“…The results of the ash study showed that the drying temperature and trevally bean powder substitution level significantly impacted the ash content of the spice powder. This is because the ash content of seasoning flour is strongly influenced by the ingredients contained therein [24] . Based on the results of the ash content analysis, the drying temperature of jack bean and jack bean flour replacement variants significantly influences the ash content of green bean fried chicken seasoning powder.…”
Section: Ash Contentmentioning
confidence: 99%